Depressive Symptomatology Mediates Associations With Community Reintegration in Veterans With TBI. Issue 6 (6th October 2016) - Moriarty, Helene; Winter, Laraine; True, Gala; Robinson, Keith; Short, Thomas H.
Abstract : Community reintegration (CR) is a challenge for military veterans with traumatic brain injury (TBI). Posttraumatic stress disorder (PTSD), depression, bodily pain, and limitations in physical functioning—common comorbidities with TBI in veterans—have all been associated with problems in CR, but their interrelationships are unclear. The role of depression as a possible mediator of effects on CR has not been examined. We tested depressive symptoms as a possible mediator of CR's associations with physical limitations, PTSD, and bodily pain. This cross-sectional study used baseline data from a larger randomized controlled trial that evaluated the impact of an in-home intervention for veterans with TBI and their families. Eighty-three military veterans with TBI recruited from a medical rehabilitation service at an urban U.S. Department of Veterans Affairs medical center participated in the study. Interview instruments measured CR, depressive symptoms, physical limitations (limitations in physical functioning), bodily pain, quality of the relationship with key family members, and sociodemographic characteristics. PTSD was determined through review of the electronic medical record. Interview data were collected in veterans' homes. Depressive symptoms totally mediated the association between physical limitations and CR and the association between PTSD and CR. The bodily pain–CR association was not significant after quality of relationship had been entered into the regression models. Findings suggest that interventions to increase CR of veterans with TBI should address depression, a treatable condition. Replication of our mediation findings in larger veteran and civilian samples with TBI is needed.